PENERAPAN ETIKA BISNIS DALAM MANAJEMEN KOPERASI DAN USAHA KECIL MENENGAH: INTEGRASI DENGAN KURIKULUM PENDIDIKAN KEWIRAUSAHAAN - Musrofah; Siti Mariah; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research examines the application of business ethics in the management of cooperatives and small and medium enterprises (SMEs) and its integration into entrepreneurship education curricula. The findings indicate that many cooperatives and SMEs in Indonesia face challenges in fully implementing business ethics due to a lack of awareness and professional management. However, cooperatives have a greater potential for ethical business practices due to their inherent principles of justice and solidarity. The integration of business ethics into entrepreneurship education has proven effective in increasing ethical awareness among business actors, contributing to the creation of responsible entrepreneurs with strong integrity. The research highlights that cooperatives and SMEs that adopt ethical business practices experience improved consumer trust, better relationships with stakeholders, and increased business sustainability. This study recommends enhancing entrepreneurship education with a focus on ethics, particularly in higher education institutions, to cultivate future entrepreneurs with a strong sense of social responsibility and ethical business conduct. Keywords: Business Ethics, Cooperative Management, Small and Medium Enterprises (SMEs), Entrepreneurship Education, Curriculum Integration